Characterization of polycyclic aromatic hydrocarbons associated with PM10 emitted from the largest composting facility in the Middle East. (2nd October 2021) - Norouzian Baghani, Abbas; Bahmani, Zohreh; Sorooshian, Armin; Farzadkia, Mahdi; Nabizadeh, Ramin; Delikhoon, Mahdieh; Barkhordari, Abdullah; Rezaei Kalantary, Roshanak; Golbaz, Somayeh; Kermani, Majid; Ashournejad, Qadir; Shahsavani, Abbas
Abstract: This work reports a characterization of PAHs-PM10, including associated health effects in the largest composting facility in Tehran, Iran. Measured PAHs-PM10 stemmed primarily from petrogenic sources with mean concentrations between 231.19 to 401.25 ng m −3 . The distribution pattern of PAHs (in terms of ring number) exhibited the following order when combining all sites: 3 > 4 > 5 > 6 > 2 rings. The average cumulative excess lifetime cancer risk values estimated for PAHs-PM10 surpassed the U.S. EPA limit (1 × 10 −6 ): refining site (3.31 × 10 −4 ) > processing site (1.75 × 10 −4 ) > aeration site (9.81 × 10 −5 ).